Effect of Mindfulness-Based Stress Reduction on burnout among nurses: A systematic review and meta-analysis of randomized controlled trials - Ani Talia; Raniindra KS. Abidin; Oscar Jayanagara (Narra Sains Indonesia, 2026)
Burnout is highly prevalent among nurses, characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment, and is associated with adverse impacts on mental health, professional performance, and quality of patient care. Mindfulness-Based Stress Reduction (MBSR) has been proposed as a potential intervention; however, evidence regarding its effectiveness across burnout dimensions remains inconsistent. The aim of this study was to systematically evaluate and quantify the effects of MBSR on burnout among nurses across the three Maslach Burnout Inventory (MBI) dimensions. A systematic search of PubMed, ScienceDirect, and the Cochrane Library was conducted up to October 2025. Eligible studies evaluated MBSR among nurses, with burnout outcomes measured using the MBI subscales: emotional exhaustion, depersonalization, and personal accomplishment. Meta-analyses were performed using inverse-variance random-effects model, with heterogeneity assessed using the I² statistic. Outcomes were categorized by follow-up duration: short-term (0–4 weeks), medium-term (>1–6 months), and long-term (>6 months). A total of seven RCTs were included in the meta-analysis. MBSR was associated with a significant reduction in emotional exhaustion overall (mean difference (MD): −5.80, 95% confidence interval (95%CI): −7.77 to −3.84; I²=26%), with the strongest effects observed in the short term (MD: −7.00), which attenuated in the medium term (MD: −5.03) and were not sustained at long-term follow-up. Depersonalization showed a modest overall reduction (MD: −2.71, 95%CI: −4.25 to −1.16), although heterogeneity was substantial (I²=70%) and effects were not maintained over time. No significant improvement was observed for personal accomplishment (MD: −0.53, 95%CI: −2.95 to 1.88; I²=88%). Risk of bias across studies was generally low to moderate, and no evidence of publication bias was identified. MBSR appears to provide short-term reductions in emotional exhaustion and may offer transient benefits for depersonalization; however, these effects diminish over time and no significant improvement is observed in personal accomplishment. These findings suggest that MBSR may function primarily as a short-term supportive intervention, and sustained reductions in burnout likely require integration with organizational strategies and ongoing support.